Pengaruh Strategi Asset-Light Terhadap Kinerja Perusahaan : Studi Perusahaan LQ45 Periode 2022 – 2024 - Pratama, Deni; Zaki, Achmad; Mustaqim, M.; Violita, Cynthia Eka (Jurnal Ekonomi, Bisnis dan Manajemen, 2026)
This study examines the effect of asset-light strategy implementation on the financial performance of companies listed in the LQ45 Index during the 2022–2024 period. The asset-light strategy is measured using Fixed Asset Turnover (FATO), Asset Structure, and Capital Expenditure (CapEx) as independent variables, while firm performance is proxied by Return on Assets (ROA). Employing a quantitative approach with a causal explanatory design, this study utilizes secondary data obtained from the audited annual financial statements of companies listed on the Indonesia Stock Exchange (IDX). Using purposive sampling, 37 companies were selected, resulting in 111 firm-year observations that met the predetermined research criteria. The data were analyzed using multiple linear regression with the assistance of SPSS version 27. The results indicate that FATO and Asset Structure have a positive and significant effect on ROA, whereas CapEx does not have a significant effect. These findings suggest that firm performance is influenced more by the effectiveness and efficiency of asset management than by the scale of capital investment itself. Therefore, companies should focus on optimizing asset productivity and maintaining an efficient asset structure to support sustainable profitability and long-term financial performance.